Concepções de planejamento de ensino : contribuições para a formação de professores - Candido, Milena dos Santos Queiróz (2017)
This work aims to investigate the prevailing conceptions of educational planning in brazilian education in order to analyze this pedagogical practice at the presente time, under the approach of historical-critical pedagogy and historical-dialetic materialism, wich was the theoric-methodologic referential adopted. Therefore, we seek to understand how the highlighted theme appears in the educational research on Brazil and how each pedagogical perspective prevalent in the brazilian education shows the educational planning. From these studies we concluded that the postmodern ideology is dominant on school education, resulting on pedagogies of “learning to learn” and its outcomes, validating ours hyphotesis. These undermine the school education since they deslegitimize the teaching, the teacher’s role, as well as the knowledges historically built by humanity and the importance of its apropriation, in addition to the denial of the need for educational planning due to its alignment to the with postmoderns referentials.